Arrests, Persistent Youth Joblessness, and Black/White Employment Differentials - Grogger, Jeff (The Review of Economics and Statistics, 1992)
Economists have long been concerned with the labor market problems of young men. Recently, research has indicated that one-fourth to one-half of all men are active in crime at some point during their youth. Furthermore, joblessness and criminal activity vary similarly by age and race. The author analyzes two data sets containing arrest and employment information to assess whether criminal activities may underlie persistent joblessness and black/white employment differential among young men. Two different approaches are taken to control for individual heterogeneity. Arrests generate some persistence in non-employment. Moreover, arrests account for nearly two-thirds of the black/white employment differential in a sample of arrestees, and nearly one-third of the difference in a more general sample. Copyright 1992 by MIT Press.